Effectiveness of control measures of Mikania micrantha on grassland: a case study from grassland in Sauraha area of Chitwan National Park - Aryal, U.; Wagle, B. H.; Lamichhane, B.; Parajuli, A.; Thapa, P. (Banko Janakari, 2018)
The spread of Mikania micrantha is causing a serious threat to native ecosystem in the tropical and sub-tropical parts of Nepal. The main objective of the study was to analyse the effectiveness of different control measures applied in the grasslands of Chitwan National Park (CNP) by comparing number and coverage of M. micrantha and native grass species. The three experimental sites were grassland of the CNP. These sites were delineated from Etrex 30, Global Positioning System (GPS) and GIS 10.3.2 in April, 2013. A block with size of 100 m x 100 m was separated by fire line on all sides for each treatment in each site. Systematic sampling with random start was used to establish sample plots within each block. Six sample plots were established in each block. The size of each plot was 2 m x 0.4 m (0.8 m2). The distance between one sample plot to another sample plot was 40 m. Three treatments applied in three blocks of each site were controlled fire, manual cutting and control (no treatment).Seedlings of M. micrantha and native grasses were counted and their coverage assessed in each plot. The coverage and number of native grass species were higher in controlled fire plot than in manual cutting and control plots. The study concludes that controlled fire is better than manual cutting and control treatments for the management of grassland. This study will help to different stakeholders to control its outreach, make polices, proper management of grasslands that are being affected by the invasion of M. micrantha. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 144-149